Possibilities of non-invasive diagnosis of diabetic peripheral polyneuropathy in children with type 1 diabetes - Г.О. Леженко; М.С. Спільник (Zdorovʹe Rebenka, 2024)
Background. Most diagnostic tests for diabetic peripheral polyneuropathy (DPNP) are not suitable for use in childhood, resulting in low diagnostic accuracy of this complication. Therefore, it is necessary to identify reliable and simple markers for early detection and monitoring of diabetic polyneuropathy progression in children. The purpose was to investigate the diagnostic value of the Clinical Neurological Examination (CNE), the pediatric-modified Total Neuropathy Score (ped-mTNS), and the Pediatric Balance Scale (PBS) in the non-invasive diagnosis of diabetic peripheral polyneuropathy in children with type 1 diabetes. Materials and methods. Ninety-one children with type 1 diabetes aged 10 to 17 years were examined. Group 1 included 57 patients with a duration of type 1 diabetes of up to 5 years, while group 2 consisted of 34 children with a disease duration of more than 5 years. To diagnose DPNP, a comprehensive neurological examination was conducted using the CNE, the ped-mTNS, and the PBS followed by determination of the diagnostic significance of each scale using ROC analysis. Results. It has been proven that two scales have diagnostic significance for identifying DPNP, the CNE and the ped-mTNS; based on the results of using both, DPNP was diagnosed in 50.5 % of patients. The clinical picture of DPNP was dominated by motor and sensory disorders, which are one of the first manifestations of this condition in children. The first signs of DPNP were registered already on the first years of illness. The frequency of development and stage of neurological disorders increased along with disease progression and the deterioration of glycemic control. Conclusions. Diabetic peripheral polyneuropathy is a common complication of diabetes in children, which is registered in 50.5 % of cases. Тhe CNE and the ped-mTNS allows to expand diagnostic capabilities regarding the detection of DPNP in children without the use of invasive diagnostic methods.